The parasitic bopyrid isopods of porcellanid crabs (Anomura: Porcellanidae) of the Colección Nacional de Crustáceos of Mexico: with the description of Aporobopyrus adriani sp. nov. and Orbimorphus boykoi sp. nov. (Epicaridea: Bopyridae) - Romero-Rodríguez, Jesús; Villalobos-Hiriart, José Luis; Álvarez, Fernando (Zootaxa, 2026)
The diversity and distribution of bopyrid isopods that parasitize porcelain crabs along both coasts of Mexico are updated based on an extensive examination of the material housed in the Colección Nacional de Crustáceos, Institute of Biology, Universidad Nacional Autónoma de México. Three hundred and sixty-seven porcelain crabs were identified as bearing one or more bopyrid in one or both of their branchial chambers; 38 were collected in the Atlantic and 329 in the Pacific. Of these, five species belong to Aporobopyrus and one to Orbimorphus. In the Mexican Atlantic, Aporobopyrus collardi and A. curtatus are recorded for the first time; in addition, we describe A. adriani sp. nov., found parasitizing four porcelain crab species, which increases the number of species in Aporobopyrus to 22. New localities on the Pacific coast are provided for A. bourdonis, A. curtatus and A. trilobatus. Orbimorphus boykoi sp. nov. is described, representing only the second species belonging to the genus. For some host species we recorded parasitized ovigerous females, their fecundity and embryos’ size. Some initial biological data on the host-parasite relationships such as prevalence, host sex and branchial chamber parasitized are reported. This study underscores the importance of scientific collections as significant sources of new information for expanding our knowledge of biodiversity and host/parasite relationships.